[La libertad de expresión] / [Francisco J. Bastida Feijedo ... (et al.)] - Bastida Freijedo, Francisco J.
Número monográfico sobre la libertad de expresión de: Derecho privado y constitución, Aǫ 4, n. 10 (septiembre-diciembre 1996)